Competitive urbanism and the limits to smart city innovation: The UK Future Cities initiative. (February 2017) - Taylor Buck, Nick; While, Aidan
The technological vision of smart urbanism has been promoted as a silver bullet for urban problems and a major market opportunity. The search is on for firms and governments to find effective and transferable demonstrations of advanced urban technology. This paper examines initiatives by the UK national government to facilitate urban technological innovation through a range of strategies, particularly the TSB Future Cities Demonstrator Competition. This case study is used to explore opportunities and tensions in the practical realisation of the smart city imaginary. Tensions are shown to be partly about the conjectural nature of the smart city debate. Attention is also drawn to weakened capacity of urban governments to control their infrastructural destiny and also constraints on the ability of the public and private sectors to innovate. The paper contributes to smart city debates by providing further evidence of the difficulties in substantiating the smart city imaginary.